PENGARUH PENERAPAN PENDEKATAN KONTEKSTUAL DENGAN BERBANTUAN SCHOOLOGY TERHADAP HASIL BELAJAR SISWA - I Dewa Putu Nyeneng; Frista Berliana Biwarno; Novinta Nurulsari (Universitas Sriwijaya, 2022)
This study aims to describe the effect of applying a contextual approach assisted by Schoology on student learning outcomes. This research was conducted at SMA Negeri 1 Tanjung Bintang using the One Group Pretest-Posttest research design. The sample of this research is students of class X MIPA 1 and X MIPA 2 SMA Negeri 1 Tanjung Bintang based on the purposive sampling technique. The research data were analyzed using normality test, hypothesis testing using Paired Sample T-Test, and N-Gain test. Based on the results of hypothesis testing using Paired Sample T-Test, the results of the analysis are significant, so it can be stated that there is an effect of applying a contextual approach assisted by Schoology on student learning outcomes. In addition, the results of the N-Gain pretest and posttest of students showed an increase in student learning outcomes in the cognitive domain with a moderate category. Thus, it can be concluded that the application of a contextual approach with the help of Schoology can improve student learning outcomes in the cognitive domain.